IDENTIFIKASI ATRIBUT KEPUASAN KONSUMEN DAN PELAYANAN RESTORAN STEAK DI KOTA BANDAR LAMPUNG - Elisa, Elisa; Hudoyo, Agus; Soelaiman, Achdiansyah (Lampung University, 2017)
The increase in income has triggered the growth of restaurants, including a steak restaurant in Bandar Lampung. This makes the competition among restaurants become harder. The purpose of this research is to identify the attributes of customer satisfactions and services in two steak restaurants in Bandar Lampung. Data were collected from 60 respondents to evaluate the satisfaction attributes and restaurant services, using questionnaires, the validity and the reliability of which have been tested. The results showed that there were 24 attributes for steak restaurants. The attributes of customer satisfactions and services including taste, menu diversity, nutrition, menu display, menu suitability, texture, menu consistency, neatness of employees, speed of service, informative waitress, hospitality, service fairness, the accuracy of written orders, payment convenience, cleanliness of the restaurant, the willingness to answer questions, responsiveness of employees, completeness cutlery, location, parking, air conditioning, toilet, variety of seating and decoration. The attributes that make consumers feel most satisfied included taste, texture, and location. Key words: attributes, consumers’ satisfactions, services, validity and reliability test